DOMESTIC WASTEWATER PLANNING STRATEGY WITH THE COMMUNAL SEPTIC TANK METHOD (TANJUNG PRIOK, NORTH JAKARTA) - Romy Setiawan, Irvan; Sembiring, Kristiana; Bangun, Sempurna; Naibaho, Pio Ranap Tua (University Muhammadiyah Jakarta, 2025)
A Communal Septic Tank is a domestic waste treatment system commonly used in densely populated areas, both in urban and rural areas. This system functions to process waste from households and commercial buildings to make it safer for the environment and human health. This research was conducted in the densely populated Sunter Agung settlement, Tanjung Priok, North Jakarta, with an area of 4.62 km², as a trial of domestic waste treatment to reduce environmental pollution and its impact on health. The process begins with community outreach, area observation, and preparation of technical documents such as working drawings and Budget Plans (RAB). Planning follows the provisions of SNI 2398:2022. The results of the data study showed that there were 85 families and 413 people. So that the need for a septic tank with a volume size of 16,000 liters / 16 cubic meters with a total of 7 tank units, each tank is equipped with 8 water absorption fields. The total budget that will be needed is IDR 991,000,000. The community will be given training in using the tank. The benefits of using communal septic tanks include improving groundwater quality, soil fertility, and preventing diseases, such as stunting. Keywords: Communal septic tanks, Domestic waste treatment, Environmental sanitation, Densely populated settlements.